Genetic Differentiation and Evolutionary Adaptation in Cryptomeria japonica. Issue 12 (1st December 2014) - Tsumura, Yoshihiko; Uchiyama, Kentaro; Moriguchi, Yoshinari; Kimura, Megumi K; Ueno, Saneyoshi; Ujino-Ihara, Tokuko
Abstract: Local adaptation of plant species is a central issue for survival during global climate change, especially for long-lived forest trees, with their lengthy regeneration time and spatially limited gene flow. Identification of loci and/or genomic regions associated with local adaptation is necessary for knowledge of both evolution and molecular breeding for climate change. Cryptomeria japonica is an important species for forestry in Japan; it has a broad natural distribution and can survive in a range of different environments. The genetic structure of 14 natural populations of this species was investigated using 3930 SNP markers. Populations on the Pacific Ocean side of Japan are clearly different from those on the Japan Sea side, as discussed in previous studies. Structure analysis and population network trees show that peripheral populations, including the most northerly and southerly ones, have unique features. We found that the genetic differentiation coefficient is low, F ST = 0.05, although it must account for the presence of important genes associated with adaptation to specific environments. In total, 208 outlier loci were detected, of which 43 were associated with environmental variables. Four clumped regions of outlier loci were detected in the genome by linkage analysis. Linkage disequilibrium (LD) was quite high in these clumps of outlier loci, which were found in linkage groups (LGs) 2, 7, 10, and 11, especially between populations of two varieties, and when interchromosomal LD was also detected. The LG7 region is characteristic of the Yakushima population, which is a large, isolated, peripheral population occupying a specific environment resulting from isolation combined with volcanic activity in the region. The detected LD may provide strong evidence for selection between varieties.